POTENSI UMKM DESA TAMBAKMAS KECAMATAN KEBONSARI KABUPATEN MADIUN MELALUI BUDIDAYA JAHE (ZINGIBER OFFICINALE) SISTEM BAG CULTURE SAMPAI PRODUK OLAHAN SENTUHAN MODERN - Nurlaili Habibi Danata; Praptiningsih Gamawati Adinurani; Djoko Setyo Martono (Universitas Merdeka Madiun, 2025)
The yard has the potential to be developed optimally to support family life used for food crops, vegetables, fruit plants, biopharmaceutical plants, livestock, and fish. In addition to meeting food and nutritional needs, it also has the potential to increase household income if designed and planned correctly. Efforts to increase family income and health can be made by cultivating biopharmaceutical plants, including ginger. Ginger plants can be grown in the yard with a Bag Culture system that is easy to maintain. Ginger plants benefit herbal drinks and can be made into various processed products with a modern touch. Community service activities start in December 2024 and run through March 2025 The activity method uses the housewises approach and field meetings to demonstrate Bag Culture cultivation systems and training in making processed products. Mentoring is carried out during the activity, and a productive yard with ginger plants is produced at the beginning of this community service program. The harvest of ginger rhizomes is used for training materials for making processed products and as a supplier of MSMEs (Micro, Small, and Medium Enterprise) to support the program to revive and develop village MSMEs.